Junie B. Jones is a beauty shop guy - Park, Barbara; Brunkus, Denise (New York : Random House, 1998)
After her first trip to a beauty parlor Junie decides she wants to work there, and she practices on her bunny slippers, her dog, and herself with disastrous results.
"A Stepping Stone book."
Keywords: Beauty shops; Hair; Kindergarten; Schools